Pharmacokinetics of amygdalin in rabbits - ZHANG Guo-ming; JIN Bao-qin (Acta Pharmacologica Sinica, 2016)
The plasma of amygdalin after iv bolus injection of 500 mg/kg into 4 rabbits decreased in 2 phases with half-lives of 3.5 and 43 min for the distributive and eliminative phases, respectively. The pharmacokinetic parameters calculated according to the two-compartment open model were: alpha=0.1997/min, beta=0.0162/min, K10=0.0291/min, K12=0.0805/min, K21=0.106/min, Vc=131 ml/kg, Vp=115 ml/kg, Vd=246 ml/kg, A=1.95 mg/ml, B=1.88 mg/ml, Clp=3.98 ml/min/kg. The above-mentioned results were similar to that obtained by postinfusion after 15 min of 500 mg/kg in 4 rabbits. The excretion of the original form of amygdalin in urine within 48 h amounted to 62%.